2017
DOI: 10.1080/14767058.2017.1315661
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of readmission rates between groups with early versus late discharge after vaginal or cesarean delivery: a retrospective analyzes of 14,460 cases

Abstract: Similar readmission rates were observed in groups with early and late discharges following vaginal or cesarean delivery without any mortality or permanent morbidity and cost analyses revealed 68 Turkish liras lower cost with early discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Bostanci Ergen et al utilized a large hospital database in Turkey to investigate the impact of early postpartum discharge, defined as 24 hours after vaginal delivery and 47 hours after cesarean delivery, on maternal postpartum readmissions. 26 The rates of readmission were similar for vaginal and cesarean deliveries combined (3% in those discharged early [ n = 6,802] vs. 2.8% in those discharged routinely [ n = 7,658]), despite including patients with home care who were discharged early and patients with pregnancy-related complications such as preeclampsia in their control group. 26 The risk of postpartum readmission after early discharge has also been investigated separately for vaginal deliveries.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Bostanci Ergen et al utilized a large hospital database in Turkey to investigate the impact of early postpartum discharge, defined as 24 hours after vaginal delivery and 47 hours after cesarean delivery, on maternal postpartum readmissions. 26 The rates of readmission were similar for vaginal and cesarean deliveries combined (3% in those discharged early [ n = 6,802] vs. 2.8% in those discharged routinely [ n = 7,658]), despite including patients with home care who were discharged early and patients with pregnancy-related complications such as preeclampsia in their control group. 26 The risk of postpartum readmission after early discharge has also been investigated separately for vaginal deliveries.…”
Section: Discussionmentioning
confidence: 93%
“…26 The rates of readmission were similar for vaginal and cesarean deliveries combined (3% in those discharged early [ n = 6,802] vs. 2.8% in those discharged routinely [ n = 7,658]), despite including patients with home care who were discharged early and patients with pregnancy-related complications such as preeclampsia in their control group. 26 The risk of postpartum readmission after early discharge has also been investigated separately for vaginal deliveries. A recent systematic review that included six randomized controlled trials in their analysis of maternal readmission rates within 6 weeks of vaginal deliveries reported a similar risk (1.6 vs. 1.3%; pooled risk ratio: 1.25, 95% CI: 0.54–2.88) for those discharged early ( n = 2,376) compared with those discharged routinely ( n = 715).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some of those negative correlations are moderately high (in absolute terms), and some are extremely high with high chances of downward biases. There are also many other studies, which have shown small or no effects of postnatal hospital stays on readmissions (Bostanci Ergen et al ., ; Bragg et al ., ; Brumfield et al ., ; Cooper et al ., ; Dalby, Williams, Hodnett, & Rush, ; Danielsen et al ., ; Gagnon et al ., ; Harron et al ., ; Johnson et al ., ; Kotagal & Tsang, ; Mandl et al ., ; Metcalfe et al ., ), breastfeeding or women's emotional well‐being (Brown et al ., ).…”
Section: Empirical Evidencementioning
confidence: 98%
“…A brief preoperative counseling was done on enhanced recovery and as a guiding principle. 10 Despite the numerous benefits proven by Brooten et al as early as the 1990s, not many developing countries have adopted such feasible and acceptable strategies. This randomized controlled trial (RCT) has shown statistically significant benefit in terms of greater maternal satisfaction, lesser hospital charges, and same rates of readmission due to maternal and neonatal complications compared to standard obstetric care.…”
Section: Clinical Settingmentioning
confidence: 99%